EFEK KONTRIBUSI STRUKTUR KEPEMILIKAN DAN KEPUTUSAN PENDANAAN DALAM MENINGKATKAN NILAI PERUSAHAAN - Awaluddin Awaluddin; Herman Sjahruddin; Masnama Tadjo; Poppy Nahdia Syahrani Pascawati (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
Ownership structure and funding decisions are determinants of company value, so this study was conducted with the intent to examine the contribution of ownership structures proxied by institutional ownership and funding decisions through debt to equity ratios as proxies in analyzing company values proxied through price to book values. The unit of analysis used is the financial statements of 18 issuers of the manufacturing sub-sector which were listed on the Indonesia Stock Exchange (BEI) in 2015-2018 (nine of them did not meet the sampling criteria). The results of data analysis provide evidence if the contribution of ownership structure that is proxied by institutional ownership is not able to increase the price to book value, the evidence has in common in explaining the contribution of a positive debt to equity ratio in increasing price to book value.